Secrets & Ciphers. - KING, KENNETH (Antioch Review)
The article discusses breach of privacy and personal information and compromised in digital arena of shared online data and passwords and mentions options for users to click consent without reading to activate software programs. Topics discussed include book "Psychopathia Sexualis" by sexologist Richard von Krafft-Ebing, laws that protect proprietary practices to maintain national sovereignty and covert surveillance required by national security.